Global Rebalancing : A Roadmap for Economic Recovery - Faruqee, Hamid (International Monetary Fund, 2013)
This book examines imbalances in seven major economies: China, France, Germany, India, Japan, the United Kingdom, and the United States, evaluating key indicators agreed on by the G20 for identifying large imbalances, including public and private debt and private saving, and countries external position. The chapters describe a suite of corrective steps tailored for each country that, if implemented, could improve prospective economic outcomes, creating sustainable and balanced growth for these economies and serving as a model for other G20 countries.